2015
DOI: 10.1088/1748-9326/10/2/024011
|View full text |Cite
|
Sign up to set email alerts
|

Tipping point of a conifer forest ecosystem under severe drought

Abstract: Drought-induced tree mortality has recently received considerable attention. Questions have arisen over the necessary intensity and duration thresholds of droughts that are sufficient to trigger rapid forest declines. The values of such tipping points leading to forest declines due to drought are presently unknown. In this study, we have evaluated the potential relationship between the level of tree growth and concurrent drought conditions with data of the tree growth-related ring width index (RWI) of the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 57 publications
3
80
0
1
Order By: Relevance
“…10.2) (Esri, Environmental Systems Research Institute, New York, NY, USA). As July is the most conducive for forest growth, and the trees in this month are most sensitive to moisture status [10,28], only the EVI for July in each year was selected to represent the status of forest growth in that year. Furthermore, the start time of the MOD13A1-EVI was 2001 [52], and the deadline of SPEIbase ver.…”
Section: Modis-enhanced Vegetation Indexmentioning
confidence: 99%
See 3 more Smart Citations
“…10.2) (Esri, Environmental Systems Research Institute, New York, NY, USA). As July is the most conducive for forest growth, and the trees in this month are most sensitive to moisture status [10,28], only the EVI for July in each year was selected to represent the status of forest growth in that year. Furthermore, the start time of the MOD13A1-EVI was 2001 [52], and the deadline of SPEIbase ver.…”
Section: Modis-enhanced Vegetation Indexmentioning
confidence: 99%
“…The effect of water balance on forest growth clearly shows hysteresis [26], and its length depends on the vegetation type, which shows distinct spatial patterns. Some researchers have found that it takes many months before the effects of moisture are apparent [10,26], and the length of such hysteresis can be a year [28,29] or even 2-3 years [63]. Due to the hysteretic effects of moisture, the SPEI was not calculated for a given time scale initially; instead, it was calculated for multiple time scales.…”
Section: Optimal Time Scale For Speimentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies of drought response timescales have been local (e.g., north-eastern Spain, parts of the United States, Thailand) or limited to select ecosystems or plant species (e.g., conifer forests in the southwest United States) [22][23][24][25][26][27][28]. A number of these studies indicate that there is variation in the strength and lag time of peak correlation between precipitation and remotely sensed LST and land surface reflectivity indices for different ecosystems.…”
Section: Introductionmentioning
confidence: 99%